A governança dos recursos hídricos no Brasil colocada à prova em situação de escassez: um estudo de caso - Kloss, Viviane Damato Otto (2015)
This work aims to study the governance of Brazilian waters, especially its operation in situations of water scarcity. For this purpose, after submission of the water crisis in the Southeast region of Brazil, which put to the test the institutional and regulatory framework of the national waters, examines the regime of the constitutional responsibilities for the environment and waters and the peculiarities related to the National System of Water Resources Management. Finally, as a suggestion, measures are identified that seek to assist in improving the governance of water and face the water crisis.